In Vivo Photoacoustic Tomography of Total Blood Flow and Potential Imaging of Cancer Angiogenesis and Hypermetabolism - Yao, Junjie (2012)
Blood flow is a key parameter in studying cancer angiogenesis and hypermetabolism. Current photoacoustic blood flow estimation methods focus on either the axial or transverse component of the flow vector. However, the Doppler angle (beam-to-flow angle) is needed to calculate the total flow speed, and it cannot always be estimated accurately in practice, especially when the system’s axial and lateral resolutions are different. To overcome this problem, we propose a method to compute the total flow speed and Doppler angle by combining the axial and transverse flow measurements. The method has been verified by flowing bovine blood in a plastic tube at various speeds and Doppler angles. The error was experimentally determined to be less than 0.3 mm/s for total flow speed, and less than 15° for the Doppler angle. In addition, the method was tested in vivo on a mouse ear. We believe that the proposed method has the potential to be used for cancer angiogenesis and hypermetabolism imaging.